THE ILLOCUTIONARY ACTS IN NARUTO’S COMIC SCRIPT - M. Afdillah Damanik; Busmin Gurning (LINGUISTICA, 2014)
ABSTRACT The study deals with the types of illocutionary acts used in Naruto’s comic script. The objectives of study were to find out the illocutionary acts, describe the most dominant type of illocutionary acts and elaborate the reason for the illocutionary acts. The data were the dialogue of Naruto to his addressees in comic Naruto. This research was conducted by using descriptive qualitative method and limited on the utterances produced by Naruto to his addresses. The findings show that there are 81 Representatives utterances,28 Expressives,27 Directives, 5 commissives and 1 Declarative. There a son of Representatives most dominantly used is Naruto gave more statements and information about his believes and the facts of the situation in the story. He often represented his believes about what happens to be the case of the conversation with others characters in the story. He also described himself and the situation of the story.   Keyword :  speech acts, illocutionary acts, comic.